THE EFFECT OF EXTRACTION TIME ON THE YIELD OF FISH OIL KEMBUNG (Rastreligersp) EXTRACTED BYWET RENDERING METHOD - Br. Sianturi1, Frisdauli junitaMargaret; Ilza, Mirna; Diharmi, Andarini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT            Fish oil is produced by extraction. The extraction methods used to obtain fish oil consist of dry and wet rendering. The success of extraction is influenced by the extraction time which affects the yield. This study aims to determine the right time with the extraction method using wet rendering of the resulting yield. The research method is an experiment using a non-factorial completely randomized design. The treatment used was the extraction time consisting of W1 (20 minutes), W2 (30 minutes), and W3 (40 minutes) at a temperature of 70oC. The analysis parameter was yield. The results showed that the yield of mackerel oil yield at 20, 30, and 40 minutes was 0.68%, 0.75%, 0.81%. The highest yield of mackerel oil was produced at a temperature of 40 minutes at 0.81%. The treatment of the length of time for mackerel oil extraction has an effect on the yield of the oil produced. Keywords:extraction, time,wet rendering, yield